The experience of the death in the kid (Journal of Parents and Teachers, 2023)
The kids are usually protected from everything related to death even though it is impossible to keep him/her completely away from it. Given this, perhaps the approach should change to face it and not to avoid talking about it. For this, here are some tips on how to deal with grief and to know some of the phases they will go through.
Keywords: phases; death; kid; duel